The integration of pre-primary education into three mainstream primary schools in the Khomas Region in Namibia: implications for management and leadership - Poulton-Busler, Richardine Masoline (Rhodes University, Faculty of Education, Department of Education, 2013)
One of the goals for Namibia's Vision 2030, through ETSIP (2005" 2015), is to establish a preprimary year in primary schools for all children aged 5" 6 to be developed first in schools serving the poorest population and OVCs. ECD is widely recognised as having a significant impact on the subsequent learning of children. The high failure and dropout rate in grade 1 made this process an important one. In 2008 the integration of ECD became a reality in five schools in the Khomas region of Namibia. At present there are 29 pilot schools in the Khomas region 29 schools, and 504 in the whole of Namibia. According to the MoE all primary schools should have a preprimary class as ECD has been recognized as a key contributor to positive outcomes in schools. This study sought to investigate various stakeholders' experiences and views of the integration of pre" primary into mainstream pre" primary schooling. The goal was to investigate the management and leadership implications of this integration. The study is an interpretive case study of three pilot primary schools. The research design made provision for data collection through semi" structured interviews, focus groups and document analysis. The main finding was that, despite numerous challenges, principals are positive about the integration of pre" primary. There is a sense of appreciation of the importance of pre" primary. Principals adopt participative and collegial management approaches in leading their schools towards becoming learning organisations. The study also uncovered several significant challenges, such as the need for more training and the provision of infrastructure to make the process more effective.
Keywords: Education, Preschool -- Namibia -- Case studies